Gluconic acid: Properties, production methods and applications—An excellent opportunity for agro-industrial by-products and waste bio-valorization. Issue 12 (December 2016) - Cañete-Rodríguez, Ana M.; Santos-Dueñas, Inés M.; Jiménez-Hornero, Jorge E.; Ehrenreich, Armin; Liebl, Wolfgang; García-García, Isidoro
Highlights: Gluconic acid and its derivatives, uses and production methods. Importance of gluconic acid derivatives as food additives. Use of renewable resources for the biobased production of gluconic acid. Comparison between fungi and bacteria for gluconic acid bioproduction. Optimized gluconic acid production by genetically modified acetic acid bacteria. Abstract: Agro-industrial by-products and wastes pose serious, widespread problems with considerable economic and environmental consequences in developed countries. However, many of the by-products contain large amounts of sugars that make them potentially excellent raw materials for the biotechnological production of added value products; in particular, by-products from perishables such as fruits can be highly useful for this aim. The growing significance and demand for gluconic acid have promoted an interest in integrating both issues as a strategy for the revalorization of these resources. The pertinence of this strategy can be better understood by examining the properties of gluconic acid and its derivatives and their uses and production methods, especially biotechnological methods, to update the existing reviews on the topic. Future advances in this direction may be promoted by the development of genetically modified organisms for the generation of new technological processes and the optimization of existing ones. Particular attention is paid to acetic acid bacteria.